Semiotics Analysis on Historical Memes in Eno Bening’s Tweet Replies - Dewanto, F. Bethavianus Bayu; Cahyono, Setyo Prasiyanto (Allure Journal, 2021)
This research is entitled Semiotics Analysis on Historical Memes in Eno Bening’s Tweet Replies. The study concerns with all the way the researchers explore the meaning of representamen/signs on either non-verbal and verbal data of historical memes in Eno Bening’s tweet replies. The method used in this paper is descriptive qualitative analysis where the researchers describe the meaning of the memes. The researchers also use semiotics analysis proposed by Pierce’s semiotic analysis (1994) in order to discover the interpretation of meaning implied in the memes. From the analysis, the researchers conclude that the historical memes in Eno Bening’s tweet replies mostly used to retell a story of historical events that happened in the past. Furthermore, memes are also used to criticize, give an opinion and also satirize a historical event.